Francuskie zastrzeżenia wobec „Moratorium Hoovera” z 20 czerwca 1931 r. - Matera, Paulina (Acta Universitatis Lodziensis. Folia Historica, 2003)
The year 1931 was particularly hard period of the Great Depression that began in October 1929. The serious crisis could be observed in Germany. It revealed in bankruptcies of many enterprises and banks. On the 26th May 1931 there was a crush in the Berlin Stock. That is why the President of the United Slates – Herbert Hoover decided to announce the one-year moratorium on all the “governmental” payments: the war debts and reparations. This decision was caused by numerous connections between American capital and Germany, but Hoover officially stated it was for improving international co-operation and economic situation of the world. All main powers approved this proposal, but the government of France submitted many reservations. According to the French point of view, moratorium was contradictory to the "Young Plan" from 1930. They wanted Germany to pay the “unconditional” part of their reparations. For the French moratorium not only provoked the danger of abandonment of reparations but also the departure from the principles of Versailles Treaty. On the 27th June 1931 in Paris the conversations between French and American politicians were begun. After many divergences, the agreement was finally reached on the 6th July. The French forced the solution that “unconditional” part of reparations would be paid to the Bank of International Settlements and would be given back to Germany as the loan. The attitude of France delayed the coming into force of moratorium. It also destroyed “ the psychological effect” of Hoover’s proposition, which did not restore confidence and spirit of international co-operation.